Forecasting future recruitment success for Atlantic cod in the warming and acidifying Barents Sea. (1st September 2017) - Koenigstein, Stefan; Dahlke, Flemming T.; Stiasny, Martina H.; Storch, Daniela; Clemmesen, Catriona; Pörtner, Hans‐Otto
Abstract: Productivity of marine fish stocks is known to be affected by environmental and ecological drivers, and global climate change is anticipated to alter recruitment success of many stocks. While the direct effects of environmental drivers on fish early life stage survival can be quantified experimentally, indirect effects in marine ecosystems and the role of adaptation are still highly uncertain. We developed an integrative model for the effects of ocean warming and acidification on the early life stages of Atlantic cod in the Barents Sea, termed SCREI ( Simulator of Cod Recruitment under Environmental Influences ). Experimental results on temperature and CO2 effects on egg fertilization, egg and larval survival and development times are incorporated. Calibration using empirical time series of egg production, temperature, food and predator abundance reproduces age‐0 recruitment over three decades. We project trajectories of recruitment success under different scenarios and quantify confidence limits based on variation in experiments. A publicly accessible web version of the SCREI model can be run underwww.oceanchange.uni-bremen.de/ ;SCREI. Severe reductions in average age‐0 recruitment success of Barents Sea cod are projected under uncompensated warming and acidification toward the middle to end of this century. Although high population stochasticity was found, considerable rates of evolutionary adaptation to acidification and shifts in organismal thermal windows would be needed to buffer impacts on recruitment. While increases in food availability may mitigate short‐term impacts, an increase in egg production achieved by stock management could provide more long‐term safety for cod recruitment success. The SCREI model provides a novel integration of multiple driver effects in different life stages and enables an estimation of uncertainty associated with interindividual and ecological variation. The model thus helps to advance toward an improved empirical foundation for quantifying climate change impacts on marine fish recruitment, relevant for ecosystem‐based assessments of marine systems under climate change. Abstract : We present a novel modeling approach for quantitative integration of environmental drivers of fish recruitment and projection of climate change impacts. We incorporate biological knowledge and experimental results for Barents Sea cod egg and larval stages. The model successfully explains empirical fluctuations of age‐0 recruitment and projects trajectories of recruitment success under different scenarios. Considerable adaptation to warming and acidification would be needed to buffer impacts on cod recruitment in the second half of the century. Management may establish a safety margin for warming and acidification impacts on cod recruitment by maintaining a high egg production of the stock.